Non-Covalent Postfunctionalization of Dye Layers on TiO2 - A Tool for Enhancing Injection in Dye-Sensitized Solar Cells - Luchs, Tobias; Zieleniewska, Anna; Kunzmann, Andreas; Schol, Peter; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
We report on newly tailored dye layers, which were employed, on one hand, for covalent deposition and, on the other hand, for non-covalently post-functionalizing TiO2 nanoparticle films. Our functionalization concept enabled intermixing a stable covalent attachment of a first layer with a highly versatile and reversible hydrogen bonding through the Hamilton receptor-cyanuric acid binding motif as a second layer. Following this concept, we integrated step-by-step a first porphyrin layer and a second porphyrin/BODIPY layer. The individual building blocks and their corresponding combinations were probed with regard to their photophysical properties, and the most promising combinations were implemented in dye-sensitized solar cells (DSSCs). Relative to the first porphyrin layer adding the second porphyrin/BODIPY layers increased the overall DSSC efficiency by up to 43 %.
CRIS-Team WoS Importer:2021-03-12